Utilization of adenosine triphosphate in rat mast cells during histamine release induced by the ionophore A23187. - Johansen, T (1979)
The role of endogenous adenosine triphosphate (ATP) in histamine release from rat mast cells induced by the ionophore A23187 in vitro has been studied. 2 The amount of histamine released by calcium from rat mast cells primed with the ionophore A23187 was dependent on the ATP content of the mast cells. 3 In aerobic experiments a drastic reduction in mast cell ATP content was found during the time when histamine release induced by A23187 takes place. 4 Anaerobic experiments were performed with metabolic inhibitors (antimycin A, oligomycin, and carbonyl cyanide p-trifluorometroxyphenylnydrazone), which are known to block the energy-dependent calcium uptake by isolated mitochondria. The mast cell ATP content was reduced during A23187-induced histamine release under anaerobic conditions in the presence of glucose. This indicates an increased utilization of ATP during the release process. 5 The observations are consistent with the view that energy requiring processes are involved in ionophore-induced histamine release from rat mast cells although part of the ATP reduction in the aerobic experiments may be due to an uncoupling effect of calcium on the oxidative phosphorylation.